2016
DOI: 10.1177/0897190016645435
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Considerations and the Role of the Clinical Pharmacist Throughout Transitions of Care for Patients With Acute Heart Failure

Abstract: Heart failure is associated with increased risk of morbidity and mortality, resulting in substantial health-care costs. Clinical pharmacists have an opportunity to reduce health-care costs and improve disease management as patients transition from inpatient to outpatient care by leading interventions to develop patient care plans, educate patients and clinicians, prevent adverse drug reactions, reconcile medications, monitor drug levels, and improve medication access and adherence. Through these methods, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Furthermore, most of these studies have utilized pharmacy services for specific high-risk populations versus all discharged patients [19,20,22,23,35,37]. This study adds to the existing but limited body of literature emphasizing a reduction in readmissions, albeit non-significant, following face-to-face pharmacist hospital follow-up visits with a multidisciplinary team in a patient-centered medical home.…”
Section: Associated Medications and American Hospital Formulary Servimentioning
confidence: 60%
“…Furthermore, most of these studies have utilized pharmacy services for specific high-risk populations versus all discharged patients [19,20,22,23,35,37]. This study adds to the existing but limited body of literature emphasizing a reduction in readmissions, albeit non-significant, following face-to-face pharmacist hospital follow-up visits with a multidisciplinary team in a patient-centered medical home.…”
Section: Associated Medications and American Hospital Formulary Servimentioning
confidence: 60%
“…It is encouraging to note that although pharmacists are absent in the wards, the participants of the study believe that pharmacists can play a role in the management of renal patients. The inclusion of a pharmacist in the renal MDT can improve renal patients’ state of health and reduce drug-related problems (McNeely 2017 ; Salgado et al 2014 ). Accordingly, participants indicated that pharmacists can review patients’ medication, work with prescribers during the prescribing stage, prevent the use of contraindicated drugs and to oversee dosage adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…Medication adherence practices are well promoted with focused group discussions. [31][32][33][34][35][36][37][38][39] Confidentiality and privacy should be maintained at all times during focused group discussions. Discussion between patients observed to be very fruitful.…”
Section: Focused Group Discussionmentioning
confidence: 99%
“…Physical verification of tablets/capsules in presence of healthcare professionals will certainly improve the understanding of the patient. [26][27][28][29][30][31][32][33][34][35][36][37][38]…”
Section: Train Patients In Clinics/hospitals For Medicine Consumptionmentioning
confidence: 99%